Pasireotide-Induced Shrinkage in GH and ACTH Secreting Pituitary Adenoma: A Systematic Review and Meta-Analysis - Mondin, Alessandro; Manara, Renzo; Voltan, Giacomo; Tizianel, Irene; Denaro, Luca; Ferrari, Marco; Barbot, Mattia; Scaroni, Carla; Ceccato, Filippo (Frontiers in Endocrinology, 2022)
Introduction: Pasireotide (PAS) is a novel somatostatin receptor ligands (SRL), used in controlling hormonal hypersecretion in both acromegaly and Cushing’s Disease (CD). In previous studies and meta-analysis, first-generation SRLs were reported to be able to induce significant tumor shrinkage only in somatotroph adenomas. This systematic review and meta-analysis aim to summarize the effect of PAS on the shrinkage of the pituitary adenomas in patients with acromegaly or CD. Materials and methods: We searched the Medline database for original studies in patients with acromegaly or CD receiving PAS as monotherapy, that assessed the proportion of significant tumor shrinkage in their series. After data extraction and analysis, a random-effect model was used to estimate pooled effects. Quality assessment was performed with a modified Joanna Briggs’s Institute tool and the risk of publication bias was addressed through Egger's regression and the three-parameter selection model. Results: The electronic search identified 179 and 122 articles respectively for acromegaly and CD. After study selection, six studies considering patients with acromegaly and three with CD fulfilled the eligibility criteria. Overall, 37.7% (95%CI: [18.7%; 61.5%]) of acromegalic patients and 41.2% (95%CI: [22.9%; 62.3%]) of CD patients achieved significant tumor shrinkage. We identified high heterogeneity, especially in acromegaly (I2 of 90% for acromegaly and 47% for CD), according to the low number of studies included. Discussion: PAS treatment is effective in reducing tumor size, especially in acromegalic patients. This result strengthens the role of PAS treatment in pituitary adenomas, particularly in those with an invasive behavior, with progressive growth and/or extrasellar extension, with a low likelihood of surgical gross-total removal, or with large postoperative residual tissue.